Midwives' Experiences in Caring for Post-Part Mothers with HIV/AIDS - Hasnia Hasnia; Yustika Rahmawati Pratami; Wiwit Vitania; Nasrianti Nasrianti; Fathia Fakhri Inayati Said; Fenska Narly Makualaina (GLOBAL HEALTH SCIENCE GROUP, 2026)
Pregnancy and the postpartum period are periods with a continuous and ongoing risk of HIV/AIDS infection, which are the targets of mother-to-child HIV prevention. Postpartum mothers with HIV positive require special care from health workers, especially midwives who are not only skilled in the technical aspects of patient care, but more than that must have empathy and be skilled in therapeutic communication. The high risk of HIV/AIDS transmission in midwives causes feelings of anxiety and reluctance to provide care to patients. Many health workers experience stress due to work, feelings of anxiety about contracting the disease, feelings of inability to meet job demands or what is expected from the job, which impacts the mental and physical health of midwives, which ultimately impacts the services provided. Objective: To explore the experiences of midwives in caring for postpartum mothers with HIV/AIDS. This type of research is qualitative with an exploratory phenomenological approach. Participants in this study were two midwives who had provided assistance to postpartum mothers with HIV/AIDS. Data collection techniques were observation, interviews, documentation, and triangulation. Data processing was carried out using the Colaizzi approach. The importance of midwives' experience in caring for postpartum mothers with HIV/AIDS will improve the midwives' ability to provide care to postpartum mothers with HIV. The midwives' ability to care for postpartum mothers with HIV/AIDS is also influenced by the midwives' experience in caring for postpartum mothers with HIV/AIDS. Some of the obstacles encountered by midwives in providing care are feelings of anxiety and shame in postpartum mothers that make sufferers disappear and refuse to undergo ANC examinations and refuse treatment. Midwives' hopes in caring for postpartum mothers with HIV/AIDS, postpartum mothers must remain enthusiastic and continue treatment to prolong life and prevent transmission to children, extra support is needed for the mother's psychology, emotional support from health workers and the patient's family. Motivation and deeper support are needed for postpartum mothers with HIV/AIDS in midwife care so that care can be carried out properly without any obstacles.